Educational Assistant Robot for Strengthening Children's Learning Using IoT - Mesquita, Iago Magalhães De; Nunes, Rhuan Da Silva; Lima, Kattiely Melo De; Salustiano, Acácio Fonseca; Silva, Wendley Souza; Paula Júnior, Iális Cavalcante De (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
Digital Information and Communication Technolo-gies (DICTs) have increasingly become part of people's daily lives, whether they are children, adults, or the elderly. However, children's unfettered and increasingly early access to these technologies has been the subject of numerous studies aimed at measuring the impacts of their usage. In parallel, another issue arises: the influence of technology on education. When using technology, children often neglect their studies due to the distractions that technological devices (such as cell phones, computers, or tablets) can cause. In light of this, and aiming to reconcile technology with education, this work seeks to present the development of an intelligent educational assistant robot using the Internet of Things (IoT), with the goal of assisting children in the educational process through active learning approaches. Thus, upon completing the development of the robot, it was possible to verify its full functionality by engaging in interactions, asking questions, and providing details on distance and temperature values.